Improve Enterprise Search using pattern matching and web mining techniques for E-Commerce Website - Goel, Archit; Verma, Neha (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
With the extensive expansion in the number of E-commerce websites, applying Web Usage Mining techniques to improve business is imperative. Also, employee as well as visitor satisfaction is important for an enterprise. This satisfaction is usually depends upon both, the effectiveness and efficiency of the search technology and how that information is published.